Access all areas? Sign language interpreting, is it that special? - Stone, Christopher (The Journal of Specialised Translation, 2010)
This article addresses some of the uniqueness and many of the similarities between working as a sign language interpreter and working as a public service interpreter in the UK. It gives a brief introduction to the history of the British Deaf community and the genesis of modern day British Sign Language (BSL). It then introduces the ever expanding areas where interpreters work and gives some examples of the care needed when working in the medical domain. It gives examples of the types of intercultural sensitivity needed by sign language interpreters and the pragmatic relevance needed in their renderings into English and BSL. Finally, it demonstrates that working with the British Deaf community is much like working with any minority language/group in the UK.